Analysis of the Implementation of Simple Financial Reports in Accordance with SAK EMKM in Salad Alvi Jember - Aprilia Fransiska Nahak; Aulia Hawa Armanto; Erlina Putri Siskawati; Intan Puspita Ashari; Madahgita Aleacasta Dynasty Azzahra Quraisy; Estu Handayani (ARTOKULO : Journal of Accounting, Economic and Management, 2024)
This research aims to examine the process of preparing financial reports for the Alvi Salad business. The focus includes obstacles faced during the preparation of the report, as well as the suitability of the report format to the SAK EMKM standards. Quantitative methods were used, combining observations, interviews and document analysis. Next, this data is analyzed to reach conclusions based on empirical findings. The results of the study confirm that Salad Alvi has deficiencies in fulfilling accounting standards. Sales records that only record goods sold show a lack of compliance with comprehensive accounting principles. In conclusion, Salad Alvi has not fully implemented a financial reporting system that complies with SAK EMKM. The financial reports prepared tend to be reactive to the owner's needs and do not reflect the accounting principles expected in SAK EMKM. Adjustments are needed so that the report preparation more closely follows the guidelines set out in the applicable accounting standards